Defining the gene expression of five predicted DNA binding proteins in Ehrlichia chaffeensis cultured in macrophages and tick cells - Knox, Cheyenne Autumn (Kansas State University, 2022)
Tick-borne diseases (TBDs) have been emerging as a major concern for the health of people and various vertebrate hosts. Pathogens such as viruses, bacteria, and parasites are transmitted from infected ticks during their bloodmeal acquisition from hosts and cause TBDs. One of the important TBDs impacting people and dogs in the USA is caused by the bacterial pathogen Ehrlichia chaffeensis. This pathogen is an obligate intracellular organism which is well adapted to tick and vertebrate hosts. Understanding how this pathogen can survive in dual hosts is important in devising methods of controlling the disease caused by it. We have been investigating how this pathogen is able to overcome the clearance by both tick and vertebrate hosts. Specifically, we use laboratory-based research involving molecular biology experiments to determine how the bacterium survives in a host. We isolated the bacterial genetic material (DNA) with proteins bound to it by performing an experiment called chromatin immunoprecipitation (CHiP). This method allows for identification of what parts of the DNA play a critical role in the bacterial survival in dual hosts. This research involved growing the bacteria using cell culture systems and by performing several molecular manipulation experiments to support our understanding of bacterial gene regulation. We focused on investigating the DNA binding proteins: MerR and EcxR, for their role in aiding the bacterial survival. We anticipate that this research will facilitate advancing the research for defining better methods of disease control and prevention.
Keywords: Ehrlichia; DNA binding protein; Ehrlichia chaffeensis; Tick borne disease